A Critical Analysis of Modern and Postmodern Philosophers at the End of History - Muhammad Asghari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article tries to critically review Modern and Postmodern Philosophers: The End of History by Ali Moradkhani. The topic of Endism is one of many new issues that in the late twentieth century, especially with Fukuyama, has gained momentum in academic circles. This issue has been, explicitly or implicitly, stated in philosophy of modern and postmodern in this book, but the author wants to make clear it under the title of "end of history". This article consists of two parts: The first part of this article refers to the shortcomings of the content of the book such as the style of its writing and translation. In other words, much of the book is a translation of the sources of the book, not necessarily the author’s own ideas. The second part of the article considers formal shortcomings of book such as book cover, table of contents, references, endnotes, etc. We also propose some samples whenever necessary.